Genetic variability for seed and seedling traits in rice (Oryza sativa) using chemical tests - Rao, P S; Kumari, A Jhansi Lakshmi; Rao, L V Subba (The Indian Journal of Agricultural Sciences, 2012)
Chemical studies involving phenol, modified phenol, Na OH and KOH on seed and GA3 and 2,4-D on seedling growth (coleoptile length) revealed great potential of these tests in assessing the variability existing among 70 varieties of rice of different ecosystems. Among the rice genotypes evaluated, japonicas exhibited negative response to phenol and modified phenol tests. However, among indica subspecies Shrabani, GR 5 Tarori Basmati, Panvel 1 and IET 14554 recorded negative response for both phenol and modified phenol test. Mahasugandha, a scented variety reacted positively for modified phenol test only. Genotypes CSR 10, IR 8, Pusa Basmati and DRR H 1 reacted negatively for NaOH test and all genotypes responded positively for KOH test. The effect of GA3 and 2,4-D on coleoptile growth of seedling was found to be highly variable among the genotypes studied. Thus these studies clearly indicate that rice genotypes exhibit wider varietal differences and the chemical tests would offer a greater potential to assess the variability existing among them.